2016
DOI: 10.1111/ijcp.12787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orlistat vs. metformin on weight loss-related clinical variables in women with PCOS: systematic review and meta-analysis

Abstract: Aims: The aim of this study was to assess the effects of orlistat on weight lossrelated clinical variables in overweight/obese women with polycystic ovary syndrome (PCOS) and to compare treatment with orlistat vs. metformin in this group. Methods: We conducted a systematic review and meta-analysis of the evidence about the use of orlistat in women with PCOS. We searched the literature published until May 2015 in MEDLINE, Cochrane Central Register of Controlled Trials and LILACS. Results: Of 3951 studies identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 61 publications
6
52
0
22
Order By: Relevance
“…Our result found that decrease serum androgen levels in the cinnamon group did not reach to a statistically significant level. This effect is similar to the observed effect of metformin as a classic insulin‐sanitizing agent that has shown to have androgen‐decreasing effect in patients with PCOS (Dumitrescu, Mehedintu, Briceag, Purcărea, & Hudita, ; Graff, Mario, Ziegelmann, & Spritzer, ).…”
Section: Discussionsupporting
confidence: 81%
“…Our result found that decrease serum androgen levels in the cinnamon group did not reach to a statistically significant level. This effect is similar to the observed effect of metformin as a classic insulin‐sanitizing agent that has shown to have androgen‐decreasing effect in patients with PCOS (Dumitrescu, Mehedintu, Briceag, Purcărea, & Hudita, ; Graff, Mario, Ziegelmann, & Spritzer, ).…”
Section: Discussionsupporting
confidence: 81%
“…Although figures vary according to the diagnostic criteria, its incidence is reported to be 6% to 20% [123]. Acne, hirsutism, seborrhoea, menstrual irregularities, anovulation, infertility, obesity, and several metabolic (e.g., glucose and lipid abnormalities) and atherosclerotic disorders are among the symptoms and signs of this disease [45].…”
Section: Introductionmentioning
confidence: 99%
“…We report that in women with PCOS, bariatric surgery‐induced weight loss, improved hirsutism, blood pressure, glycaemic and lipid profile. Orlistat improved anthropometric, endocrine and metabolic outcomes when compared to placebo but not metformin . However, we acknowledge that there is encouraging evidence in the general population showing that bariatric surgery improves weight loss and metabolic outcomes such as glycaemic control, lipid profile and blood pressure .…”
Section: Discussionmentioning
confidence: 80%
“…Meta‐analysis of the studies comparing orlistat to placebo was not possible but the systematic review reported improvements in anthropometric (BMI, weight, waist circumference or waist‐hip ratio), endocrine (testosterone) and metabolic outcomes (triglycerides, HDL, LDL, HOMA‐IR and insulin). Meta‐analysis of the studies comparing orlistat to metformin showed no significant differences . Psychological outcomes were not assessed by the above review.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation